Effects of Integrating Care for Medicare-Medicaid Dually Eligible Seniors in Minnesota. Issue 1 (2nd January 2020) - Anderson, Wayne L.; Long, Sharon K.; Feng, Zhanlian
ABSTRACT: Individuals dually eligible for Medicare and Medicaid often receive fragmented and inefficient care. Using Minnesota fee-for-service claims, managed care encounters, and enrollment data for 2010–2012, we estimated the likely impact of Minnesota Senior Health Option (MSHO)—seen as the first statewide fully integrated Medicare-Medicaid model—on health care and long-term services and supports use, relative to Minnesota Senior Care Plus (MSC+), a Medicaid-only managed care plan with Medicare fee for service. Estimates suggest that MSHO enrollees had significantly higher use of primary care and, potentially, of community-based services, combined with lower use of hospital-based care than similar MSC+ enrollees. Adopting fully integrated care models like MSHO may have merit in other states.